Atrial Cardiomyopathy: From Diagnosis to Treatment - Zheyu Liu; Tao Liu; Gang Wu (Reviews in Cardiovascular Medicine)
With a better understanding of the susceptibility to atrial fibrillation (AF) and the thrombogenicity of the left atrium, the concept of atrial cardiomyopathy (ACM) has emerged. The conventional viewpoint holds that AF-associated hemodynamic disturbances and thrombus formation in the left atrial appendage are the primary causes of cardiogenic embolism events. However, substantial evidence suggests that the relationship between cardiogenic embolism and AF is not so absolute, and that ACM may be an important, underestimated contributor to cardiogenic embolism events. Chronic inflammation, oxidative stress response, lipid accumulation, and fibrosis leading to ACM form the foundation for AF. Furthermore, persistent AF can exacerbate structural and electrical remodeling, as well as mechanical dysfunction of the atria, creating a vicious cycle. To date, the relationship between ACM, AF, and cardiogenic embolism remains unclear. Additionally, many clinicians still lack a comprehensive understanding of the concept of ACM. In this review, we first appraise the definition of ACM and subsequently summarize the noninvasive and feasible diagnostic techniques and criteria for clinical practice. These include imaging modalities such as echocardiography and cardiac magnetic resonance imaging, as well as electrocardiograms, serum biomarkers, and existing practical diagnostic criteria. Finally, we discuss management strategies for ACM, encompassing “upstream therapy” targeting risk factors, identifying and providing appropriate anticoagulation for patients at high risk of stroke/systemic embolism events, and controlling heart rhythm along with potential atrial substrate improvements.